Long-term persistence of supernumerary B chromosomes in multiple species of Astyanax fish - Silva, Duílio Mazzoni Zerbinato de Andrade [UNESP] (2021)
Background: Eukaryote genomes frequently harbor supernumerary B chromosomes in addition to the “standard” A chromosome set. B chromosomes are thought to arise as byproducts of genome rearrangements and have mostly been considered intraspecific oddities. However, their evolutionary transcendence beyond species level has remained untested. Results: Here we reveal that the large metacentric B chromosomes reported in several fish species of the genus Astyanax arose in a common ancestor at least 4 million years ago. We generated transcriptomes of A. scabripinnis and A. paranae 0B and 1B individuals and used these assemblies as a reference for mapping all gDNA and RNA libraries to quantify coverage differences between B-lacking and B-carrying genomes. We show that the B chromosomes of A. scabripinnis and A. paranae share 19 protein-coding genes, of which 14 and 11 were also present in the B chromosomes of A. bockmanni and A. fasciatus, respectively. Our search for B-specific single-nucleotide polymorphisms (SNPs) identified the presence of B-derived transcripts in B-carrying ovaries, 80% of which belonged to nobox, a gene involved in oogenesis regulation. Importantly, the B chromosome nobox paralog is expressed > 30× more than the A chromosome paralog. This indicates that the normal regulation of this gene is altered in B-carrying females, which could potentially facilitate B inheritance at higher rates than Mendelian law prediction. Conclusions: Taken together, our results demonstrate the long-term survival of B chromosomes despite their lack of regular pairing and segregation during meiosis and that they can endure episodes of population divergence leading to species formation.